2010
DOI: 10.1021/je100552a
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of the Binary Mixtures of 1,2-Dichloroethane with Chlorobenzene and Bromobenzene from (298.15 to 313.15) K

Abstract: Densities, viscosities, and refractive indices for the binary mixtures of 1,2-dichloroethane with chlorobenzene and bromobenzene have been determined from (298.15 to 313.15) K over the entire range of concentration at atmospheric pressure. Excess molar volumes have been calculated from the experimental data and fitted to a Redlich-Kister polynomial function. The ability of the Prigogine-Flory-Patterson (PFP) theory to predict V m E at 303.15 K has been tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…As it can be shown in Table , our experimental pure compound density results, at various temperatures, compare well to the corresponding literature data. The overall experimental density results, for the pure compounds, are summarized in Table .…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…As it can be shown in Table , our experimental pure compound density results, at various temperatures, compare well to the corresponding literature data. The overall experimental density results, for the pure compounds, are summarized in Table .…”
Section: Resultssupporting
confidence: 83%
“…A survey of the open literature reveals many reports regarding the volumetric properties of binary mixtures containing EGDME, DEGDME, or DEGDEE, confirming the interest for these chemicals. To our best knowledge, no density and V E data have been reported yet, for the binary mixtures investigated, except for the 1,2-DCE + EGDME binary system …”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…We used the LennardJones parameters estimated by the method of Chung et al (Chung et al, 1988) to provide the parameters that are reported in Table 1, and fit the data of Paniego and Pinto to obtain the Fc reported in Table 2. In the liquid phase, we selected Thorpe and Rodger (Thorpe & Rodger, 1894), Batschinski (Batschinski, 1913), Ni et al (Ni, Su, Wang, & Qiu, 2010), and Malhotra et al (Malhotra, Price, Woolf, & Easteal, 1990) for the determination of the parameters reported in Table 2. Although generally it is best to use a reference fluid that is most chemically similar to the fluid of interest, in this case we found better results with propane as a reference fluid especially at higher pressures, rather than R134a, so propane was selected even though it is not halogenated.…”
Section: R1243zf (333-trifluoropropene)mentioning
confidence: 99%